Road traffic accidents in the Kandy police area and its economic implications - Dharmaratne, S.D (My University, 2001)
1520 vehicles were involved in these 949 accidents. The commonest vehicle to be involved was the van (26.1 per cent) while the motor car was second. The public transport vehicles, which comprised private (PVT) bus, Sri Lanka Transport board (SLTB) bus and the three wheeler (TW) accounted for 35.3 per cent of all the vehicles. Only 4.5 per cent motorcycles (MCs) and 0.7 per cent pedal cycles being involved in these accidents may reflect their low use in the study area. These accidents killed or injured 353 road users. The commonest road user to be injured was the pedestrian (53.6 per cent) followed by the passenger (27.2 per cent).These accidents killed ten (2.8 per cent) road users and grievously injured 75 (21.2 per cent) road users. The total estimated cost of the 949 accidents was Rs.359,87,336.61 with the fatal accidents being most costly (Rs. 181,55,250.82). As road user error was identified as the main cause of these RTAs, in the prevention of them this has to be addressed. One important, practical and affordable measure in this aspect is the prevention of the pedestrian coming into contact with the motor vehicle. Therefore, keeping the pedestrians away from the road areas reserved for motor vehicle as far as possible and insisting that buses have closed doors when they are in motion are some of the recommendations made based on this study